2014
DOI: 10.1177/1060028014539919
|View full text |Cite
|
Sign up to set email alerts
|

Time Course of Calcium Concentrations and Risk Factors for Hypocalcemia in Patients Receiving Denosumab for the Treatment of Bone Metastases From Cancer

Abstract: Our results support more frequent monitoring of serum calcium concentrations at baseline and during the first 2 weeks of treatment in patients receiving denosumab, especially those with an eGFR <30 mL/min.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 52 publications
2
37
2
Order By: Relevance
“…To identify risk factors for hypocalcemia, we first compared various baseline clinical demographic parameters between hypocalcemic and normocalcemic patients following denosumab administration. Although patients who developed hypocalcemia had normal baseline calcium concentrations, the mean was slightly lower than in those who did not have normal baseline calcium concentrations, consistent with recent findings by Autio et al26 In contrast, other reports found no significant difference in baseline serum corrected calcium concentration between hypocalcemic and normocalcemic groups 17,18. Nevertheless, hypocalcemia should be corrected prior to administration of denosumab.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…To identify risk factors for hypocalcemia, we first compared various baseline clinical demographic parameters between hypocalcemic and normocalcemic patients following denosumab administration. Although patients who developed hypocalcemia had normal baseline calcium concentrations, the mean was slightly lower than in those who did not have normal baseline calcium concentrations, consistent with recent findings by Autio et al26 In contrast, other reports found no significant difference in baseline serum corrected calcium concentration between hypocalcemic and normocalcemic groups 17,18. Nevertheless, hypocalcemia should be corrected prior to administration of denosumab.…”
Section: Discussionsupporting
confidence: 86%
“…This may be explained by most patients having low bone turnover after the first course of denosumab. Furthermore, some previous studies17,18 have reported that prior use of zoledronic acid reduced the incidence of denosumab-induced hypocalcemia. Although they provided other reasons, this effect is most likely because of the induction of low bone turnover after zoledronic acid administration.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Denosumab-induced hypocalcaemia can last weeks to months despite therapy requiring frequent monitoring. The risk of hypocalcaemia has been found to be highest in the first 2 weeks 14. High doses of calcium and vitamin D are typically given for treatment.…”
Section: Discussionmentioning
confidence: 99%